2022
DOI: 10.1186/s12870-022-03476-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the CCT gene family in Chinese white pear (Pyrus bretschneideri Rehd.) and characterization of PbPRR2 in response to varying light signals

Abstract: Background Canopy architecture is critical in determining the light environment and subsequently the photosynthetic productivity of fruit crops. Numerous CCT domain-containing genes are crucial for plant adaptive responses to diverse environmental cues. Two CCT genes, the orthologues of AtPRR5 in pear, have been reported to be strongly correlated with photosynthetic performance under distinct canopy microclimates. However, knowledge concerning the specific expression patterns and roles of pear … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…In our previous study, we found that the flat-type trellis system (double primary branches above the row, DP) presented higher net photosynthetic rates, and photosynthesis, carbohydrate catabolic processes and fatty acid metabolic processes were overrepresented in the leaves of DP systems with open-canopy characteristics [ 17 ]. PpPRR5 was shown to be associated with negatively regulating photosynthetic performance under distinct training systems [ 18 ]. However, the mechanism by which canopy architecture affects pear fruit quality is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that the flat-type trellis system (double primary branches above the row, DP) presented higher net photosynthetic rates, and photosynthesis, carbohydrate catabolic processes and fatty acid metabolic processes were overrepresented in the leaves of DP systems with open-canopy characteristics [ 17 ]. PpPRR5 was shown to be associated with negatively regulating photosynthetic performance under distinct training systems [ 18 ]. However, the mechanism by which canopy architecture affects pear fruit quality is not fully understood.…”
Section: Introductionmentioning
confidence: 99%